Access to and Uptake of HIV Prevention Services among Men who have Sex with Men (MSM) in Targeted Intervention (TI) Program Districts, Nepal. (2014)
SUMMARY: Nepal faces concentrated HIV epidemic. The National Centre for AIDS and STD Control (NCASC) has estimated that there are 40,723 people living with HIV (PLHIV) in Nepal in 2013 with adult HIV prevalence 0.23% (NCASC, 2014). The existing National HIV/AIDS Strategy (2011-2016) identifies people who inject drugs (PWID), female sex workers (FSWs) and their clients, migrant workers and their spouses and men who have sex men (MSM) as key affected population (NCASC, 2012). This study was designed to understand an existing situation of the access to and uptake of Targeted Intervention (TI) HIV services among MSM and also identify the barriers and facilitators to access and uptake of those intervention services in Nepal. A qualitative cross-sectional study was conducted in Banke, Kailali, Kaski, Kathmandu and Morang districts that represent five development regions of Nepal. In total 30 MSM, 13 service providers, and 15 district and five central level policy makers were interviewed using pretested interview checklists. The MSM study sample comprised of MSM 18 years and above reporting having anal or oral sex with another male in the 12 months preceding the study with diverse socio-demographic backgrounds (marital status, education, occupations) including those MSM who were not exposed to the current TI HIV program. All interviews were audio recorded with the consent of study participants and all audio records were transcribed verbatim in Nepali and then translated to English. Data were organized using Atlas ti version 6 qualitative data management software and coded using a thematic analysis procedure. Analysis was done by predefined themes and sub-themes which emerged during the data processing and analysis. The quotations included in the report best represent the range of ideas voiced around key themes. Individual consent was sought before interviews.